PENGARUH PEMBERIAN PUPUK GUANO TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SAWI DI TANAH INCEPTISOL - Siregar, Ganda Parasian; Armaini, Armaini; Wardati, Wardati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The use of Guano fertilizer in the cultivation of mustard plant in the soil of Inceptisol is the part of effort organic fertilizer giving that come from bat feces. This fertilizer is espected to improve the mustard growth, because it has function as the source of nutrient and it is able to improve the physical and biological properties of soil. The research was carried out on the experimental station, Fakulty of Agriculture, University of Riau on March-April 2018, by using a completely randomized design with the treatment of Guano fertilizer dosage (0, 300, 600, 900, 1.200) g.m-2. The growth observed was plant height, number and area of heaves, total plant weight and weight of plant suitable for consumption. The result showed that giving of Guano fertilizer effect on parameter of plant height, number and area of leaves, total weight and weight of plant suitable for comsumption. The best treatment was obtained a dose of 1.200 g.m-2 and it was able to increase the yield by 48,92 % compared to without being given Guano.Key word :Mustard plant, Guano fertilizer, Yields